A comprehensive evaluation framework on the economic performance of state-owned enterprises - Farhad Taghizadeh-Hesary; Naoyuki Yoshino; Chul Ju Kim; Aline Mortha (Asian Development Bank Institute (ADBI), 2019)
State-owned enterprises (SOEs) play a key role in the economy of many countries. They are usually thought to be in charge of increasing social welfare. At the same time, their relatively low performance poses several problems, including slowing down economic growth. This effect is especially pronounced in countries where such firms represent a large share of the economy. Therefore, it is crucial for central governments to implement a comprehensive evaluation method to assess the performance of SOEs. Previous studies have offered many ways to evaluate their performance. By employing the principal component analysis technique and using data of 1,148 SOEs, mostly from European countries, our study aims at providing a more comprehensive framework for assessing SOE performance that includes various factors. We selected five factors: profitability, per capita productivity, per capita costs, debt due days, and solvency. The results of our empirical study show that solvency, per capita costs, and per employee productivity have more deterministic power over the success or failure of SOEs, compared to profitability. While profit making of SOEs is important, focusing on profitability as the solve assessment criterion will mislead policy makers, keeping in mind also that the nature of many SOEs is to generate social welfare and not profit.
Keywords: H11; P11; L32; 330; state-owned enterprises; SOEs; performance assessment; public economics